2007
DOI: 10.1146/annurev.ecolsys.38.091206.095808
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Carbon–Cycle Feedback to Climate Warming

Abstract: The coupled carbon-climate models reported in the literature all demonstrate a positive feedback between terrestrial carbon cycles and climate warming. A primary mechanism underlying the modeled positive feedback is the kinetic sensitivity of photosynthesis and respiration to temperature. Field experiments, however, suggest much richer mechanisms driving ecosystem responses to climate warming, including extended growing seasons, enhanced nutrient availability, shifted species composition, and altered ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
424
4
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 468 publications
(438 citation statements)
references
References 153 publications
(172 reference statements)
8
424
4
2
Order By: Relevance
“…While temperature influences almost all ecosystem processes , it is still not well understood whether or not climate warming would stimulate net ecosystem carbon (C) release, accelerate buildup of atmospheric CO 2 concentration, and then amplify climate warming (Luo 2007). Global models that couple climate change with C cycles all predicted a positive feedback that climate warming accerelates CO 2 buildup in the amtosphere by 20 -200 ppmv and amplifies climate warming by 0.1 to 1.5 °C (Friedlingstein et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While temperature influences almost all ecosystem processes , it is still not well understood whether or not climate warming would stimulate net ecosystem carbon (C) release, accelerate buildup of atmospheric CO 2 concentration, and then amplify climate warming (Luo 2007). Global models that couple climate change with C cycles all predicted a positive feedback that climate warming accerelates CO 2 buildup in the amtosphere by 20 -200 ppmv and amplifies climate warming by 0.1 to 1.5 °C (Friedlingstein et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Another study, based on natural forest stands in New Zealand, found an AWP increase of between 5 and 20 • C −1 for forests, assuming no change in forest structure and species composition (Coomes et al, 2014). The analysed plots were spread throughout New Zealand, and warmer temperatures coincided with higher radiation (Mackintosh, 2016). Hence, the analysed temperature effect also includes the influence of radiation.…”
Section: The Study Designmentioning
confidence: 94%
“…In the case of higher mean annual temperature, we observe an elongation of the vegetation period. This leads to higher forest productivity (if other resources are not limiting (Luo, 2007) and explains why SI MAT is often positive. However, warmer summer temperatures can also lead to a F. J.…”
Section: The Study Designmentioning
confidence: 99%
See 2 more Smart Citations